(untitled) (Mustansiria Dental Journal, 2018)
The objective of this study aimed to assess the carieslike lesion preventive potential of low power dye assisted He-Ne laser. Enamel of extracted human premolar teeth were painted with methylene blue dye and irradiated with 5 mW of He-Ne laser, which emitted laser with 632.8 nm in wavelength. Another group were irradiated without dye application, and the third group was served as control (without laser irradiation). All samples were subjected to carieslike lesion formation by 3.5 pH lactic acid for 21 days. The crowns after that were sectioned into ground cross sections and the lesion depths were measured under a polarizing microscope. According to this study, successful carieslike lesion inhibition could be achieved to 29% extent, by using low power dye assisted He-Ne laser irradiation.